Aspergillus fumigatus exoβ(1‐3)glucanases family GH55 are essential for conidial cell wall morphogenesis. (30th August 2019) - Millet, Nicolas; Moya‐Nilges, Maryse; Sachse, Martin; Krijnse Locker, Jacomina; Latgé, Jean‐Paul; Mouyna, Isabelle
Abstract: The cell wall of Aspergillus fumigatus is predominantly composed of polysaccharides. The central fibrillar core of the cell wall is composed of a branched β(1‐3)glucan, to which the chitin and the galactomannan are covalently bound. Softening of the cell wall is an essential event during fungal morphogenesis, wherein rigid cell wall structures are cleaved by glycosyl hydrolases. In this study, we characterised the role of the glycosyl hydrolase GH55 members in A. fumigatus fungal morphogenesis. We showed that deletion of the six genes of the GH55 family stopped conidial cell wall maturation at the beginning of the development process, leading to abrogation of conidial separation: the shape of conidia became ovoid, and germination was delayed. In conclusion, the reorganisation and structuring of the conidial cell wall mediated by members of the GH55 family is essential for their maturation, normal dissemination, and germination.